Wellness cluster and knowledge-based economy (Research Announcements "Heritage BG", 2025)
The objective of this material is to analyse the complete content of the Bulgarian Wellness cluster and its connection to the social environment for building a knowledge-based economy. The necessity for the widespread dissemination of Wellness culture within society has been established. Our focus on the Wellness Cluster divides the structural elements into reactive and proactive procedures and Wellness impacts. We explain how Niche practices and impacts stand out from the conventional healthcare sector (also known as the disease industry). The standardization of tools and definitions in the research is crucial for scientific progress in creating a knowledge-based economy in Bulgaria. References:Chipeva 2019: Chipeva, Maya. Авангард Прима: Avangard Prima: Kango dzhŭmps Aerobika, Sofia. ISBN 978-619-239-131-7Ignatova 2022: Ignatova, Darinka. Nadeshdni instrumenti pri otsenka na uchilishten Uelnes (Wellness) v nachalen etap na osnovnata obrasovatelna stepen. Strategies for Policy in Science & Education, 30 (1), 70-81. https://doi.org/10.53656/str2022-1-4-relPolimenov 2022: Polimenov Mincho. Politiki v obrasovanieto po turisŭm, kompetentsii i stimuli sa rasvitie. Strategies for Policy in Science and Education, 30 (3), 133-145. Available at: https://doi.org/10.53656/str2022-3-7-touTomova 2021: Tomova, Tatiana. Menstrualni narusheniya – rasprostranenie i proyavlenie. Meshdunarodno nauchno spisanie Smart Innovations in Recreational, Wellness Industry and Niche Tourism. 3(2), 33-38 (In Bulgarian). еISSN 2603-493X (onlain). Available at: https://scjournalbg. globalwaterhealth.org/Tsanov 2015: Tsanov, Ivan. Ikonomika na sporta, Sofiya, BAK, 17-26Dimitrova 2019: Dimitrova, Bistra. Quality assessment about standards for wellness services and certified skills of specialized staff. Original scientific paper. DOI: 10.15547 / tjs.2019.02.007. Trakia Journal of Sciences, Vol. 17, No 2, 2019, 143-149, ISSN: 1313-3551 (online) / http://tru.uni-sz.bg/tsj/Vol.17Dimitrova 2020: Dimitrova, Bistra. Relationships between education and innovations in the recreational Industry in Bulgaria. Original scientific paper. DOI: 10.15547 / tjs.2019.02.007. Trakia Journal of Sciences, No 18 /2, 143-149, ISSN: 1313-3551 (online) / http://tru.uni-sz.bg/tsj/Dimitrova 2023: Dimitrova, Bistra. Educational policy, specialised staff, innovations and recreational industry. Strategies for Policy in Science and Education, Volume 31, Number 5, 532-546, 2023. https://doi.org/10.53656/str2023-5-6-impGWI 2021: Global Wellness Institute. The Glоbal Wellness Ecоnоmy: Lооking Beyоnd CОVID. Ed. Glоbal Wellness Institute, December 2021. Available at: https://glоbalwellnessinstitute.оrg/industry-research/the-glоbal-wellness-ecоnоmy-lооking-beyоnd-cоvid/Harizanova 2022: Harizanova, Olya. New scientific infrastructure for innovations on the creative and recreation industries. Smart innovations in the Recreational, Wellness Industry and Niche Tourism Journal, 4 (1-2), 17-21.Ignatova, Iliev 2020: Ignatova, Darinka, Alexandar Iliev. Motor qualities and their influence on children’s development. International Scientific Journal: Smart Innovations in Recreation, Wellness Industry and Niche Tourism, No 2 (1-2), p: 16-44. ISSN: 2603-4921 (online). Available at: https://scjournal. globalwaterhealth.org.Ignatova, Iliev 2022: Ignatova, Darinka, Alexandar Iliev. Benchmarking for thedevelopment of speed and power characteristics. Strategies for Policy in Science and Education, 30 (4), 411-421. https://doi.org/10.53656/str2022-4-6-benNesheva 2020: Nesheva Irina. Information system for inclusion of women with normal pregnancy in gymnastics program. ‘Smart Innovations on the Recreative & Wellness Industries and Niche tourism’, Sofia, No 2 (1), 33 39. eISSN: 2603-4921. Available at: https://scjournal.globalwaterhealth.org/Nesheva 2023: Nesheva, Irina. Study of results between initial and final specific tests In women with normal pregnancy. Trakia Journal of Sciences, Sofia. No 17 (2), 135-142. Available at: http://tru.uni-sz.bg/tsj/Vol.17,%20Suppl.2,%202019/6.pdfPolimenov 2019: Polimenov Mincho. Transfer of innovation in the service technology for increasing the restaurant quality product. International ScientificjournalSmartInnovations inRecreational, Wellness Industry and Niche Tourism. Vol.1, Issue 2, 29 -35, ISSN 2603-4921 (online). Available at: https://scjournal.globalwaterhealth.org/
Keywords: Wellness culture; Cluster; Business environment; Tourism; Wellbeing index